The Rise of Translanguaging in EFL Contexts: A Bibliometric Study Using Scopus Database (2013–2025) - Habibie, Alvons; Datunsolang, Fadila Amalia; Jhems Richard Hasan (Universitas Negeri Medan, 2025)
This study aims to examine publication trends, citation patterns, leading authors and institutions, geographic distribution, and emerging thematic clusters in research on translanguaging pedagogy in English as a Foreign Language (EFL). Using a bibliometric approach, data were retrieved from the Scopus database from 2013 to 2025. A total of 143 peer-reviewed articles that met the inclusion criteria were analyzed quantitatively. The findings reveal a significant increase in publication volume, particularly since 2018, reaching its peak in 2024. The most highly cited articles explored multilingual identity, teacher strategies in EFL classrooms, and technology, particularly Google Translate, in translingual contexts. Asian countries, especially Indonesia, China, and Thailand, accounted for the most publications, while notable contributions came from institutions in Southeast Asia, Europe, and North America. Topic visualization using VOSviewer identified seven major thematic clusters: classroom interaction, student perceptions, teacher identity, multimodality, bilingual education, and academic writing in EFL. These results indicate that translanguaging has evolved beyond a linguistic strategy into a comprehensive and context-sensitive pedagogical approach. The study highlights the need for further longitudinal research and calls for deeper investigation into integrating translanguaging in curriculum development and teacher training across various educational levels.